Efectivity Evaluation among Dengue Control Programs in Semarang City, Indonesia (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2020)
Increased dengue cases occur throughout Southeast Asia. Semarang Health Office held programs to control dengue,which are Rainfall monitoring,Routine Mosquito Larvae Monitoring Program, One House One Larvae Observer Movement, And Students look For Mosquito Larvae Movement. To assess whether the programs reducing Dengue Hemorrhagic Fever caseswere effective. The method used were correlation analysis. Data obtained from every region in Semarang and reported to Semarang Health Office. Average Dengue Hemorrhagic Fever case was 79.5Â±13.69. Correlationtest results between dengue cases with rainfall was r=0.951;p=0.049, Larvae Absence Rate from Routine Mosquito Larvae Monitoring Program was r=0.648;p=0.352, with Larvae Absence Rate from One House One Larvae Observer Movement was r=0.804;p=0.196, with Larvae Absence Rate from Students Search For Mosquito Larvae Movement was r=0.961;p=0.039. Correlation between rainfall and Larvae Absence Rate from Students Search For Mosquito Larvae Movement with Dengue Hemorrhagic Fever case were significant and had positive strong correlation,correlation test results of Larvae Absence Rate from Routine Mosquito Larvae Program and One House One Larvae Observer Movement had strong correlation but were not significant.